Green logistics practices in Malaysian food-based manufacturing industry - Hussin, Hilda (2015)
Logistics has been regarded as a key determinant to business performance over the past 50 years. However, the increase in environmental concerns over pollution, climate change, congestion, waste disposal, and resource depletion among others have triggered an increased attention from the government and society. Business operations such as sourcing, manufacturing and logistics are believed to be responsible for most of the environmental problems. Besides, growing demand of customers and environmental societies for more environmental friendly products have led ‘green’ become a common practice to portray the environmental friendly image of products,processes, systems and technologies, and the way business is conducted. Therefore,green logistics practices were conceptualized concerning the production and distribution of goods in a sustainable way, taking into account the environmental and social factors. The main objective study is to investigate green logistics practices in food-based manufacturing industry in Malaysia. The addresses of food-based manufacturers were obtained from the list of Federation of Malaysian Manufacturers (FFM) Directory 2010. Census sampling technique was used in this study and data collected from 155 food-based manufacturers throughout Malaysia. Statistical analyses such as descriptive analysis, green manual analysis, factor analysis, and multiple regression analysis were used in this study. In this study, green manual with European Guideline (2007) was used to determine the level of green logistics practices among Malaysian food-based manufacturers and to identify which of the green logistics practices need critical review from the manufacturers. From the analysis, the result shows that the Malaysian food-based manufacturers had implemented green practices in three logistics activities namely;transportation and distribution; warehousing, material handling and information processing and last but not least in packaging and reverse logistics activity. From the analysis, it was found that majority of the Malaysian food-based manufacturers green logistics practices fall into light green colour band for each one of three logistics activities. This colour band indicated that the manufacturers have practiced green in their logistics activities and they are well on the way to operating “green logistics practices” but still need to adopt the remaining green practices. The ultimate finding of this study also showed overall Malaysian food-based manufacturers green practices logistics level by taking into account all three selected logistics activities. From the green manual analysis, the result showed that out of 155 manufacturers, about 54% of manufacturers logistics practices fall into light green colour band, 39% pale light green and the remaining categorized as green (7%). Besides that, green manual analysis has identified three infrequent green logistics practices that rarer implement in manufacturers’ logistics activities namely; manufacturer unusual used alternative fuel such as biofuel or biodiesel in their vehicle, manufacturer less install and use dedicated blast freezing chambers for frozen or chilled storage to accelerate the speed of product freeze and lastly only few manufacturer making business transaction with supplier that execute recycle program. In addition, the results from factor analysis shows Malaysian food-based manufacturers implemented green practices because they were motivated by three factors namely environment motivational factor, economy motivational factors and social motivational factor. In addition, the findings showed that the manufacturers obtained several perceived benefits when applying green in their logistics activities. All the benefits are apparent into three perspectives as well like what have motivated them to practice green. The three benefits are economy, environment, and social benefits perspectives. Last but not least, the relations of all the motivational (three factors) and perceived benefits (three factors) obtained were examined with the manufacturers’ green logistics practices level. The result showed that out of six factors that investigated, only one had a significant relationship with green logistics practices level. From the multiple regression analysis, the result showed that environment benefits factor become the utmost pressure that influence the manufacturers’ green logistics practices level,followed by economy (cost) benefits factor and next economy (cost) motivation factor. The subsequently factors that influenced the level of green logistics practices are social motivation factor and social benefits factor.